2004
DOI: 10.1021/jf049770a
|View full text |Cite
|
Sign up to set email alerts
|

Radical Scavenging Activities of Peels and Pulps from cv. Golden Delicious Apples as Related to Their Phenolic Composition

Abstract: The relationship between phenolic composition and radical scavenging activity of apple peel and pulp was investigated in fruit produced according to both organic and integrated agricultural methods. Apple tissue extracts were subjected to high-performance liquid chromatography separation, which showed that as compared with pulps, peels are richer in almost all of the quantified phenolics. Flavonols, flavanols, procyanidins, dihydrochalcones, and hydroxycinnamates were the identified phenolic classes in peel ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
169
5
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(225 citation statements)
references
References 33 publications
(40 reference statements)
40
169
5
4
Order By: Relevance
“…In contrast, Chinnici et al measured higher concentrations of hydroxycinnamic acids in apple cv. 'Golden Delicious' grown in integrated production than in apple from organic production [24].…”
Section: Table IVmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Chinnici et al measured higher concentrations of hydroxycinnamic acids in apple cv. 'Golden Delicious' grown in integrated production than in apple from organic production [24].…”
Section: Table IVmentioning
confidence: 99%
“…In apple pulp, contents of flavonols were essentially lower than in peel and, moreover, organically produced apples contained higher levels in comparison with the other three treatments. However, Chinnini et al, who compared contents of phenolic compounds in apple peel and pulp in regard to the applied management system, detected higher concentrations of flavonols in apples of integrated production compared with those produced organically, both in apple peel and pulp [24]. On the other hand, Slatnar et al reported that the concentration of flavonols was not dependent on infection with apple scab [25] and Mikulic Petkovsek et al determined that cultivars resistant to apple scab contained lower contents of quercetin 3-rhamonoside [19]; flavonols may not play a key role in the defense against apple scab.…”
Section: Table IVmentioning
confidence: 99%
“…Chinnici et al (2004) encontraram valores totais de flavanóis (equivalente à catequina) de 223 ± 26,4 e 46,1 ± 9,22 mg.kg -1 em peso fresco, para maçã descascada e polpa de maçã, respectivamente. Esses valores são superiores aos encontrados em nosso estudo.…”
Section: Determinação De Flavanóis E Atividade Antioxidanteunclassified
“…During the past decade the apple polyphenols have been subjected to a number of investigations due to their presence in human diet and their biological properties and benefit effects on health. Phenolic compounds seem to protect against cardiovascular disease and have certain potential anticarcinogenic properties due to their antioxidant activity and their function as free radical scavengers [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%